How Do Canadian Budget Forecasts Compare with Those of Other Industrial Countries? - Muhleisen, Martin; Danninger, Stephan; Hauner, David; Krajnyak, Kornelia (Washington, D.C. : International Monetary Fund, 2005)
This paper compares Canadian central government budget forecasting with forecasting by other industrial countries. While fiscal forecasting in Canada is governed by one of the strongest institutional frameworks, quantitative analysis suggests that budget projections of macroeconomic and fiscal aggregates have been more cautious than in other countries since the mid-1990s. The relatively volatile macroeconomic environment as well as institutional factors, such as Canada's asymmetric deficit target, have likely contributed to this outcome.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet